Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER) dan Price Book Value (PBV) Terhadap Harga Saham Pada Industri Semen yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2013-2017 - Nopi Kamelia Sari (Universitas Batanghari Jambi, 2019)
The development of the Earning Per Share (EPS) on the cement industry which fluctuate. The development of the Price Earning Ratio (PER) on the cement industry is increasing. This research is a desciptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical test F test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free. Simultaneously, PER EPS and PBV effect on share prices on cement industry registered in BEI 2013-2017 period. EPS, PER and PBV just give influence on the share price of 73.5%, while the remaining 26.5% are influenced by factors other than this research. EPS can deliver a positive influence against the stock price. This is evidenced by the value t calculate larger than t table (4.925 > 2.119). PER do not give a positive and significant effect against the stock price. This is evidenced by the value t calculate the smaller of the t table (-1,572 < 2.119). PBV gives a positive and significant influence against the stock price. This is evidenced by the value t calculate larger than t table (2,542 < 2.119. As for the suggestion that the author can provide in this research, the company should further enhance the value of EPS on the company again, because in this study indicated that the EPS give influence on the increase in share price and for researchers next another ratio should use to calculate its effect on stock prices because it can be made possible another ratio also influenced the increase of the company's stock price.